The Trans-Pacific Partnership agreement (TPP) negotiations : overview and prospects - Elms, Deborah (2012)
The Trans-Pacific Partnership (TPP) is a trade agreement currently under negotiation between nine countries in three continents, including Australia, Brunei, Chile, Malaysia, New Zealand, Peru, Singapore, United States and Vietnam. In late 2011 three additional countries--Japan, Canada and Mexico--announced their intention to join as well. The TPP has always been called a "high quality, 21st century" agreement that covers a range of topics not always found in free trade agreements. This includes not just trade in goods, services and investment, but also intellectual property rights, government procurement, labor, environment, regulations, and small and medium enterprises. This paper traces the complex negotiations and evolution of the talks since the early 2000s to the present.